Electron‐acoustic solitons and double layers in the inner magnetosphere. Issue 10 (29th May 2017) - Vasko, I. Y.; Agapitov, O. V.; Mozer, F. S.; Bonnell, J. W.; Artemyev, A. V.; Krasnoselskikh, V. V.; Reeves, G.; Hospodarsky, G.
Abstract: The Van Allen Probes observe generally two types of electrostatic solitary waves (ESW) contributing to the broadband electrostatic wave activity in the nightside inner magnetosphere. ESW with symmetric bipolar parallel electric field are electron phase space holes. The nature of ESW with asymmetric bipolar (and almost unipolar) parallel electric field has remained puzzling. To address their nature, we consider a particular event observed by Van Allen Probes to argue that during the broadband wave activity electrons with energy above 200 eV provide the dominant contribution to the total electron density, while the density of cold electrons (below a few eV) is less than a few tenths of the total electron density. We show that velocities of the asymmetric ESW are close to velocity of electron‐acoustic waves (existing due to the presence of cold and hot electrons) and follow the Korteweg‐de Vries (KdV) dispersion relation derived for the observed plasma conditions (electron energy spectrum is a power law between about 100 eV and 10 keV and Maxwellian above 10 keV). The ESW spatial scales are in general agreement with the KdV theory. We interpret the asymmetric ESW in terms of electron‐acoustic solitons and double layers (shocks waves). Key Points: Electrostatic solitary waves with asymmetric bipolar parallel electric field contribute to broadband wave activity in inner magnetosphere Asymmetric ESW follow KdV dispersion relation and have spatial scales comparable to those of electron‐acoustic solitons Asymmetric ESW are interpreted in terms of electron‐acoustic solitons and electron‐acoustic shock waves